The Effect of Family Ownership and Institutional Ownership on Agency fees in Manufacturing Companies Listed on the Indonesia Stock Exchange - Angel Sri Meilinda; Makhdalena Makhdalena; Fenny Trisnawati (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
This study aims to determine the effect of family ownership and institutional ownership on agency costs in manufacturing companies listed on the Indonesia Stock Exchange. This research was conducted at manufacturing companies in the food and beverage sub-sector that were listed on the Indonesia Stock Exchange (IDX) for 2018-2022 which had complete data (family ownership, institutional ownership and SGA) of 9 companies with 45 years of observation. This research used a descriptive approach quantitative and non-parametric statistical tests with the Spearman approach. Data processing using SPSS software version 16.0. The results show that family ownership and institutional ownership are not significant to agency costs. Family Ownership has a very weak correlation to agency costs. Meanwhile, family ownership has a very high correlation with agency costs. Family ownership has a negative relationship direction. Meanwhile, institutional ownership has a positive relationship direction. With reference to the results of this study, companies need to increase the activities of institutional investors in carrying out supervision in carrying out collective actions so that agency costs can be reduced because low agency costs are very important for companies to attract investors and are considered to provide satisfactory feedback. for investors.